(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article has shown that diction by the author is a lynchpin in setting up the tone for any work an author creates. It starts by defining what exactly diction is: its various constituents being vocabulary, syntax, and formality-and it has highlighted how these choices influence the emotional response a reader will have with the text. The article discusses how each style of language-formal, informal, colloquial, concrete, abstract, and poetic-affects the mood and tone of a piece of writing. He also explores how diction operates across genres, from drama to poetry, showing its versatility in the conveyance of atmosphere and emotion.